Peningkatan Kemampuan Bahasa Melalui Metode Mendongeng Pada Anak Usia Dini di TK Ihya Al-UIum Kota Makassar - Nurhidaya S, A. Rezky; Nasaruddin, Nasaruddin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
Language ability is an essential aspect of early childhood development and needs to be stimulated through appropriate learning methods. This study aimed to improve language skills through the storytelling method in early childhood at TK Ihya Al-Ulum, Makassar City. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were children aged 4-6 years. Data were collected through observation, performance assessment, and documentation. The results indicated that the application of the storytelling method improved children’s language abilities, particularly in listening, speaking, and vocabulary development. The improvement was observed gradually from the pre-cycle to Cycle I and showed significant progress in Cycle II. These findings conclude that the storytelling method is effective as a meaningful and enjoyable language learning strategy for early childhood education.